Метод визначення степенів утворюючих поліномів псевдовипадкових двійкових послідовностей - Олещук, Д. В.; Бондар, Д. В. (ХНУРЕ, 2025)
This work is devoted to the description of the method of programmatic determination of the powers of the generating polynomials of pseudo-random binary sequences, according to which the cell numbers of the shift register of the sequence generator are selected. The algorithms for creating tuples of register bit numbers and selecting from them those that can be used to generate pseudo random binary sequences are considered. There is a link to the developed software module. The advantages and disadvantages of the considered method are formulated.
Keywords: псевдовипадкова двійкова послідовність; утворюючий поліном